Predictors of Progression-Free Survival and Local Tumor Control after Percutaneous Thermal Ablation of Oligometastatic Breast Cancer: Retrospective Study - Ridouani, Fourat; Solomon, Stephen B; Bryce, Yolanda; Bromberg, Jacqueline F; Sofocleous, Constantinos T; Deipolyi, Amy R (Journal of vascular and interventional radiology, 2020)
To describe ablation of bone, liver, lung, and soft tissue tumors from oligometastatic breast cancer and to define predictors of local progression and progression-free survival (PFS). A total of 33 women (mean age 52 ± 12 years old; range, 28-69 years), underwent 46 thermal ablations of liver (n = 35), lung (n = 7), and bone/soft tissue (n = 4) metastases. Mean tumor diameter was 18 ± 15 mm (range, 6-50 mm). Ablations were performed to eradicate all evident sites of disease (n = 24) or to control growing sites in the setting of other stable or responding sites of disease (n = 22). Patient characteristics, ablation margins, imaging responses, and cases of PFS were assessed. Follow-up imaging was performed using contrast-enhanced computed tomography (CT), magnetic resonance (MR) imaging, or positron-emission tomography/ CT. Median PFS was 10 months (95% confidence interval [CI], 6.2 -14.5 months), and time to local progression was 11 months (95% CI, 5-16 months). Eight patients (24%) maintained no evidence of disease during a median follow-up period of 39 months. Ablation margin ≥5 mm was associated with no local tumor progression. Longer PFS was noted in estrogen receptor-positive patients (12 vs 4 months; P = .037) and younger patients (12 vs 4 months; P = .039) treated to eradicate all sites of disease (13 vs 5 months; P = .05). Eighteen patients (55%) developed new metastases during study follow-up. Thermal ablation of oligometastatic pulmonary, hepatic, bone, and soft tissue tumors can eliminate local tumor progression if margins are ≥5 mm. Longer PFS was observed in patients who were estrogen receptor-positive and patients who were younger and in whom all sites of disease were eradicated.